Pengukuran MTF (Modulation Transfer Function) berdasarkan LSF (Line Spread Function) dan PSF (Point Spread Function) pada pesawat PET/CT dan SPECT/CT - Sharah Nataz Shilfa; M. Roslan Abdul Gani; Intan Apriliani Syaridatul Mu’minah; Fery Ardiansyah; Lukmanda Evan Lubis; Djarwani Soeharso Soejoko (Journal of Medical Physics and Biophysics, 2019)
This study aims to know the value of MTF obtained by using two methods: LSF (Line Spread Function) and PSF (Point Spread Function) on PET/CT and SPECT/CT. Measurement done with LSF method performed by thin flood source 18F or 99mTc 12 mCi, while PSF using thin line source 18F atau 99mTc 2 mCi with diameter 0.5 mm. The MTF calculations are performed based on image profile, for PET/CT assisted by 3 filter types and 4 reconstruction algorithms while SPECT/CT based on collimator variation. MTF calculation method have done based on Tsujioka et al. (2014) by combining the ImageJ, MATLAB, and Origin spreadsheet. System performance is determined at 10% MTF. The measurement results on PET/CT showed MTF highest value obtained by the Butterworth filter and reconstruction algorithm Iterative, Iterative 3D, and Backprojection with identical MTF value (0.155 cycles/mm) for LSF method, while PSF method by using Butterworth filter and Backprojection reconstruction algorithm obtained value 0.15 cycles/mm. In SPECT/CT, the second detector with LEHR collimator give MTF value to the LSF method and PSF method sequently 0.104 cycles/mm and 0075 cycles/mm. Based on the advantages and disadvantages of both methods, generally the PSF method is recommended as a spatial resolution QC program for nuclear medicine modalities.